Effect of plastic anisotropy of ZK60 magnesium alloy sheet on its forming characteristics during deep drawing process. Issue 5 (February 2017) - Lin, Peng; Sun, Ying; Chi, Chengzhong; Wang, Wenxian
Abstract The plastic anisotropy of a ZK60 magnesium alloy sheet was investigated using uniaxial tensile tests and deep drawing tests. The earing behavior of the sheet during deep drawing was studied by both experimental and finite element analyses. The ZK60 alloy sheet exhibits higher plastic strain ratio (r ) value in 45° than those in 0° and 90° to rolling direction, and ther value decreases with temperature increasing in various loading directions. A negative planar anisotropy (△r ) value results in earing in 45° to rolling direction. Higher absolute value of △r leads to larger average earing ratios. With drawing ratio (DR) increasing, the average earing ratio first increases to a peak and then drops, showing a bell-shape curve. The average earing ratio of cylindrical drawn cup increases as the deep drawing proceeds. At the shoulder region of drawn cups, the most reduction in thickness strain occurs in 45° to rolling direction of the sheet. At the necking region, the minimum thickness strain in 0° is lower than those in 45° and 90° directions. At the thickening region, the minimum thickness strain in 45° is lower than those in 0° and 90° directions due to the large circumferential compression stress and the large negative value of planar anisotropy △r value.